The effect of sleep fragmentation on the perception of experimentally-induced deep muscle pain in women with primary dysmenorrhoea and healthy controls - Flinn, Chloe Eliza (My University, 2018)
The relationship between sleep and pain is bidirectional: sleep disturbances lead to increased pain sensitivity and increased pain disrupts sleep. Women with primary dysmenorrhoea experience monthly recurrent menstrual pain, associated with sleep disturbances, which could contribute to increased pain sensitivity. The present study aimed to determine the effect of sleep fragmentation on the perception of experimentally-induced deep-muscle pain during a pain-free phase of the menstrual cycle in women with severe primary dysmenorrhoea compared to pain-free controls. Following an interview process and one-week screening phase, ten women with primary dysmenorrhoea (22 ± 3y) and nine healthy controls matched for age (21 ± 3y), visited the Wits Sleep Laboratory on four occasions, in a randomised order, during the pain-free follicular phase; an adaptation, a baseline (uninterrupted sleep), and two consecutive sleep fragmentation nights (disrupted sleep). Each morning, perception of experimentally-induced deep-muscle pain was assessed using: a) the submaximal effort tourniquet test (forearm ischaemia), and b) intramuscular injection of hypertonic saline in an area within (lower back) and outside (forearm) of referred menstrual pain. Sensitivity to deep-muscle pain did not differ between groups after the baseline night. However, after one night of sleep fragmentation, women with dysmenorrhoea experienced an increase in hypertonic saline-induced forearm muscle pain sensitivity compared with the controls (p = 0.01), and both groups of women experienced an increase in ischaemic pain sensitivity compared to baseline (p ≤ 0.05). Sensitivity to hypertonic saline-induced pain within the lower back was not altered by sleep fragmentation. Pain sensitivity returned to baseline levels after the second night of sleep fragmentation. These findings provide support for a relationship between disrupted sleep and pain sensitivity, however, effects of sleep fragmentation are mixed; depending on duration of sleep fragmentation, pain modality, and whether women have primary dysmenorrhoea.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Medicine. Johannesburg,